Lithium iron phosphate electrode material and preparation method and application thereof
By forming a polydopamine coating layer on the surface of lithium iron phosphate material and forming an N-doped carbon coating layer, the problem of poor rate performance of lithium iron phosphate electrode material is solved, and the effect of high rate performance and high energy density is achieved, which is suitable for industrial applications of power batteries.
Patent Information
- Application Number
- CN202411675001.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-28
AI Technical Summary
Lithium iron phosphate electrode materials have problems of poor rate performance and low energy density, which limits their wide range of applications in power batteries.
The dynamic performance and rate performance of the material are improved by forming a uniform polydopamine coating on the surface of the lithium iron phosphate material and forming an N-doped carbon coating through high temperature calcination.
It achieves the improvement of the rate performance of the material while ensuring capacity, taking into account high compaction, high discharge specific capacity and high rate performance, and is suitable for large-scale industrial production.
Smart Images

Figure CN119542386A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a lithium iron phosphate electrode material and a preparation method and application thereof, belonging to the technical field of electrode materials. Background Art
[0002] Lithium iron phosphate has the advantages of being environmentally friendly, having excellent cycle performance, having no memory effect and being cheap, but it has the disadvantages of poor rate performance due to low diffusion coefficient and low conductivity, and low energy density due to low tap density. The above disadvantages seriously hinder the commercial production of lithium iron phosphate cathode materials. Currently, commercial lithium iron phosphate cathode materials cannot have good rate performance while meeting high energy density, which seriously limits the large-scale application of lithium iron phosphate cathode materials as power batteries.
[0003] In response to the above problems, coating lithium iron phosphate materials with a carbon layer with good conductivity can effectively improve the kinetic properties of lithium iron phosphate materials, thereby improving the rate performance of the material while ensuring the capacity. However, conventional carbon layer coating has limited improvement in the rate performance of lithium iron phosphate materials. Too thick a coating layer will reduce the compaction density of the material and hinder the passage of lithium ions, resulting in a decrease in the discharge specific capacity. Studies have shown that coating lithium iron phosphate with carbon materials with good electronic and ionic conductivity, such as graphene or carbon nanotubes, can effectively avoid reducing the compaction density of the material and greatly improve the electrochemical reaction kinetics of the material, but the production cost of these materials is high and they are not suitable for large-scale industrial production.
[0004] Chinese patent document CN117088348A discloses a method for carbon-coated modified lithium iron phosphate positive electrode. The method for carbon-coated modified lithium iron phosphate positive electrode disclosed in the patent document comprises the following steps: dispersing a carbon source (dopamine hydrochloride) in an ethanol-water mixed solution and ultrasonically dispersing it for 30 minutes to obtain a carbon source suspension, adding a LiFePO4 positive electrode material to the carbon source suspension and ultrasonically dispersing it for 60 minutes to obtain a suspension, and drying the suspension for 4 hours to obtain a precursor B; wherein the volume ratio of anhydrous ethanol to deionized water in the ethanol-water mixed solution is 1:1, the concentration of the carbon source suspension is 10g / L and 15g / L, and the amount of carbon source added is 10% and 15% of the mass of the LiFePO4 positive electrode material, respectively; then the precursor B is ground and placed in an argon atmosphere, and sintered at a high temperature of 650°C for 3 hours to obtain a carbon-coated modified lithium iron phosphate active component LiFePO4 / C. Compared with lithium iron phosphate, the carbon-coated modified lithium iron phosphate prepared in the patent document has higher capacity, cycle stability and rate performance. However, in order to better meet the requirements of power battery use, it is necessary to further improve the rate performance of lithium iron phosphate. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a lithium iron phosphate electrode material, so as to further improve the rate performance of carbon-coated modified lithium iron phosphate prepared by the current conventional method.
[0006] The second object of the present invention is to provide a lithium iron phosphate electrode material to further improve the rate performance of carbon-coated modified lithium iron phosphate.
[0007] The third object of the present invention is to provide an application of a lithium iron phosphate electrode material as a positive electrode material for a lithium battery, so as to further improve the rate performance of the carbon-coated modified lithium iron phosphate when used as a positive electrode material for a lithium battery.
[0008] In order to achieve the above objectives, the technical solution adopted by the method for preparing the lithium iron phosphate electrode material of the present invention is:
[0009] A method for preparing a lithium iron phosphate electrode material comprises the following steps: mixing a lithium iron phosphate suspension and a dopamine hydrochloride solution so that the dopamine hydrochloride self-polymerizes on the surface of the lithium iron phosphate to form polydopamine, then performing solid-liquid separation, and then calcining the solid obtained by solid separation to obtain the lithium iron phosphate electrode material; the primary particle size of the lithium iron phosphate is 200-400 nm, and the ratio of the mass of the lithium iron phosphate in the lithium iron phosphate suspension to the mass of the dopamine hydrochloride in the dopamine hydrochloride solution is (2-3):(0.004-0.02).
[0010] In the preparation method of the lithium iron phosphate electrode material of the present invention, a layer of polydopamine with a thickness of about 2 nm uniformly coated on the surface of the lithium iron phosphate is formed by the self-polymerization effect of dopamine hydrochloride, and a three-dimensional structure N-doped carbon coating layer is formed on the basis of retaining the original carbon layer after high-temperature calcination. Heteroatom doping can form vacancies in the carbon material, and the N element has a strong electronegativity, which can improve the electronic conductivity of the carbon layer, thereby improving the rate performance of the material. By selecting the particle size of the lithium iron phosphate and the amount of dopamine hydrochloride, a coating layer of suitable thickness can be formed on the surface of the lithium iron phosphate, thereby avoiding particle agglomeration, and improving the rate performance and discharge specific capacity of the material, taking into account the high compaction, high discharge specific capacity and high rate performance of the material.
[0011] Preferably, the primary particle size of lithium iron phosphate is 200-230 nm, and the ratio of the mass of lithium iron phosphate in the lithium iron phosphate suspension to the mass of dopamine hydrochloride in the dopamine hydrochloride solution is 3:(0.010-0.018); the primary particle size of lithium iron phosphate is 250 nm, and the ratio of the mass of lithium iron phosphate in the lithium iron phosphate suspension to the mass of dopamine hydrochloride in the dopamine hydrochloride solution is 3:(0.012-0.015); the primary particle size of lithium iron phosphate is 400 nm, and the ratio of the mass of lithium iron phosphate in the lithium iron phosphate suspension to the mass of dopamine hydrochloride in the dopamine hydrochloride solution is 2:(0.005-0.007).
[0012] Preferably, the dopamine hydrochloride solution is prepared by mixing dopamine hydrochloride and a buffer solution, and the buffer solution is a tris(hydroxymethyl)aminomethane hydrochloride buffer solution.
[0013] Preferably, the carbon content on the surface of lithium iron phosphate is not more than 2%.
[0014] Preferably, the mass fraction of the lithium iron phosphate suspension is 2% to 3%.
[0015] Preferably, the lithium iron phosphate suspension and the dopamine hydrochloride solution are mixed for 12 to 16 hours.
[0016] Preferably, the calcination temperature is 650-750° C. and the calcination time is 8-12 hours.
[0017] Preferably, the heating rate from room temperature to the calcination temperature is 5-10° C. / min.
[0018] The technical solution adopted by the lithium iron phosphate electrode material of the present invention is:
[0019] A lithium iron phosphate electrode material prepared by the above-mentioned method for preparing the lithium iron phosphate electrode material.
[0020] The lithium iron phosphate electrode material of the present invention has the advantages of high compaction, high discharge specific capacity and high rate performance.
[0021] The technical solution adopted by the application of the lithium iron phosphate electrode material of the present invention as a positive electrode material for a lithium battery is:
[0022] A use of the lithium iron phosphate electrode material prepared by the preparation method of the lithium iron phosphate electrode material as a positive electrode material for a lithium battery.
[0023] When the lithium iron phosphate electrode material of the present invention is used as a positive electrode material for a lithium battery, the discharge specific capacity and rate performance of the battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is an appearance morphology diagram of the lithium iron phosphate electrode material prepared in Example 1 of the present invention;
[0025] Figure 2 This is an appearance morphology diagram of the lithium iron phosphate electrode material prepared in Example 2 of the present invention;
[0026] Figure 3 This is an appearance morphology picture of the lithium iron phosphate electrode material prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0027] The preparation method of the lithium iron phosphate electrode material of the present invention is a pioneering invention. In the preparation method of the lithium iron phosphate electrode material of the present invention, a layer of uniformly coated polydopamine is formed on the surface of the lithium iron phosphate by utilizing the self-polymerization effect of dopamine hydrochloride, and a three-dimensional structure N-doped carbon coating layer is formed on the basis of retaining the original carbon layer after high-temperature calcination. Heteroatom doping can form vacancies in the carbon material, and the N element has a strong electronegativity, which can improve the electronic conductivity of the carbon layer, thereby improving the rate performance of the material. For lithium iron phosphates of different particle sizes, different masses of dopamine hydrochloride need to be used to form a coating layer of suitable thickness, thereby avoiding particle agglomeration, and improving the rate performance and discharge specific capacity of the material, taking into account the high compaction, high discharge specific capacity and high rate performance of the material.
[0028] The preparation method of the lithium iron phosphate electrode material of the present invention ensures that dopamine can be evenly coated on the surface of particles through the self-polymerization of dopamine in Tris buffer, thereby avoiding agglomeration of particles during secondary calcination. During the calcination process, the commercial lithium iron phosphate coated with dopamine hydrochloride can form a nitrogen-doped carbon-coated three-dimensional conductive network on the basis of the original coating layer. The coating layer with a three-dimensional structure has an excellent transmission effect on ions and electrons. At the same time, the large-area conductive network can increase the specific surface area of the material, improve the liquid retention of the positive electrode material, and thus improve the lithium ion diffusion kinetics.
[0029] The present invention uses dopamine hydrochloride as the original coating material. Compared with conventional carbon sources, the N-atom-doped carbon layer obtained after high-temperature carbonization of dopamine hydrochloride has better electronic conductivity. N atoms have strong electronegativity, which can promote the increase of defect sites in carbon materials and provide more deintercalation channels for lithium ions. Compared with two-dimensional high-conductivity materials such as graphene or carbon nanotubes, dopamine hydrochloride has lower raw material costs and lower coating amounts, thereby ensuring that the compaction density of the positive electrode material does not change significantly. The present invention provides a method for preparing a lithium iron phosphate positive electrode material with good rate performance, including the raw materials used, modification methods, and process specifications. The raw materials include the grain size, particle size distribution, and carbon content of the raw materials (the smaller the primary particle size of the base material, the thicker the coating layer is required to avoid particle agglomeration); the modification method includes the modified raw materials used, the modification process, and the amount of the modified raw materials added; the process specifications include the calcination temperature and time of the material.
[0030] Compared with the traditional graphene or carbon nanotube coating scheme, the coating material obtained by the present invention has lower cost and less coating amount; compared with the common power-type materials, the preparation method of the lithium iron phosphate electrode material of the present invention is simple and feasible, the cost is controllable, the modification effect is good, and it can be mass-produced; compared with the common power-type materials, the present invention can take into account both high discharge specific capacity and high rate performance, greatly improving the application potential of lithium iron phosphate materials as power-type battery materials. Compared with the common power-type lithium iron phosphate positive electrode materials, the present invention takes into account low cost, high production efficiency and high rate performance.
[0031] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0032] 1. Specific embodiments of the lithium iron phosphate electrode material and the preparation method thereof of the present invention are as follows:
[0033] Example 1
[0034] The preparation method of the lithium iron phosphate electrode material of this embodiment specifically includes the following steps:
[0035] (1) Weigh 2.428 g of tris(hydroxymethyl)aminomethane hydrochloride (Tris), dissolve it in 100 mL of concentrated NaOH solution (the mass fraction of the NaOH solution is 60%), then add dilute hydrochloric acid (prepared by 0.84 mL of 37% hydrochloric acid and an appropriate amount of water to make a 100 mL solution), and adjust the pH of the solution to 8.5 to obtain a Tris buffer;
[0036] (2) adding 2 g of commercial lithium iron phosphate material (surface carbon content ≤ 2% wt) with a primary particle size of 400 nm to 100 mL of deionized water, and ultrasonically dispersing at 25° C. for 1 h to obtain a lithium iron phosphate suspension;
[0037] (3) Dissolve 0.006 g of dopamine hydrochloride in the Tris buffer prepared in step (1) to obtain a dopamine hydrochloride solution; add the lithium iron phosphate suspension to the dopamine hydrochloride solution, and stir at a constant temperature of 25°C for 16 hours to allow dopamine hydrochloride to self-polymerize on the surface of the lithium iron phosphate to form polydopamine, then centrifuge and clean the stirred system to collect the polydopamine-coated lithium iron phosphate nanoparticles, i.e., LiFePO4@PDA; finally, dry the LiFePO4@PDA powder in an 80°C forced air drying oven for 12 hours, and then grind it to obtain particles, and then heat the particles to 650°C in an argon atmosphere at a heating rate of 5°C / min and calcine them for 12 hours to obtain a lithium iron phosphate electrode material (N-doped carbon-coated lithium iron phosphate positive electrode material). The appearance morphology of the lithium iron phosphate electrode material prepared in this embodiment is as follows: Figure 1 shown.
[0038] Example 2
[0039] The only difference between the preparation method of the lithium iron phosphate electrode material of this embodiment and the preparation method of the lithium iron phosphate electrode material of Example 1 is that the mass of dopamine hydrochloride used in this embodiment is 0.004 g. The appearance of the lithium iron phosphate electrode material prepared in this embodiment is as follows: Figure 2 shown.
[0040] Example 3
[0041] The preparation method of the lithium iron phosphate electrode material of this embodiment specifically includes the following steps:
[0042] (1) Weigh 2.428 g of tris(hydroxymethyl)aminomethane hydrochloride (Tris), dissolve it in 100 mL of concentrated NaOH solution (the mass fraction of the NaOH solution is 60%), then add dilute hydrochloric acid (prepared by 0.84 mL of 37% hydrochloric acid and an appropriate amount of water to make a 100 mL solution), and adjust the pH of the solution to 8.5 to obtain a Tris buffer;
[0043] (2) adding 3 g of commercial lithium iron phosphate material (surface carbon content ≤ 2% wt) with a primary particle size of 250 nm to 100 mL of deionized water, and ultrasonically dispersing at 25° C. for 1 h to obtain a lithium iron phosphate suspension;
[0044] (3) Dissolve 0.015 g of dopamine hydrochloride in the Tris buffer prepared in step (1) to obtain a dopamine hydrochloride solution; add the lithium iron phosphate suspension to the dopamine hydrochloride solution, and stir at a constant temperature of 25°C for 12 hours to allow dopamine hydrochloride to self-polymerize on the surface of the lithium iron phosphate to form polydopamine, then centrifuge and clean the stirred system to collect the polydopamine-coated lithium iron phosphate nanoparticles, i.e., LiFePO4@PDA; finally, dry the LiFePO4@PDA powder in an 80°C forced air drying oven for 12 hours, and then grind it to obtain particles, and then heat the particles to 750°C in an argon atmosphere at a heating rate of 10°C / min and calcine them at this temperature for 8 hours to obtain a lithium iron phosphate electrode material (N-doped carbon-coated lithium iron phosphate positive electrode material). The appearance morphology of the lithium iron phosphate electrode material prepared in this embodiment is as follows: Figure 3 As shown. Figure 1-3 It can be concluded that the self-polymerization of dopamine in Tris buffer ensures that dopamine can be evenly coated on the surface of the particles and avoids the agglomeration of particles during the secondary sintering process.
[0045] Example 4
[0046] The only difference between the preparation method of the lithium iron phosphate electrode material of this embodiment and the preparation method of the lithium iron phosphate electrode material of Example 3 is that the primary particle size of the commercial lithium iron phosphate material used in this embodiment is 230 nm.
[0047] In other embodiments (Examples 5-20), the quality and parameters of the raw materials used in the preparation method (primary particle size of lithium iron phosphate) and the process parameters are changed, and the quality and process parameters of each raw material used in Examples 1-20 are summarized in Table 1.
[0048] Table 1 The quality of each raw material used in Examples 1-20 and the process parameters
[0049]
[0050] Comparative Example 1
[0051] The lithium iron phosphate electrode material of this comparative example is the commercial lithium iron phosphate material used in Example 1 with a primary particle size of 400 nm.
[0052] Comparative Example 2
[0053] The lithium iron phosphate electrode material of this comparative example is the commercial lithium iron phosphate material with a primary particle size of 230 nm used in Example 4.
[0054] Comparative Example 3
[0055] The only difference between the preparation method of the lithium iron phosphate electrode material of this comparative example and the preparation method of the lithium iron phosphate electrode material of Example 1 is that step (1) is omitted in the preparation method of the lithium iron phosphate electrode material of this comparative example, and the Tris buffer used in step (3) is replaced by an aqueous solution of ethanol (the volume ratio of ethanol to water is 1:1).
[0056] 2. Specific examples of the application of the lithium iron phosphate electrode material of the present invention as a positive electrode material for lithium batteries are as follows:
[0057] The lithium iron phosphate electrode material prepared in any one of Examples 1-20 can be used as a positive electrode material for a lithium battery.
[0058] Experimental example
[0059] In order to evaluate the application effect of the lithium iron phosphate electrode material prepared in each embodiment and comparative example as a positive electrode material for a lithium battery, the lithium iron phosphate electrode material in each embodiment and comparative example is assembled with a metal lithium sheet and an electrolyte into a CR2032 button battery. The specific preparation process is as follows: based on the total mass of the positive electrode material as 100%, the positive electrode material, the conductive agent SP, the binder (the mass ratio of the positive electrode material, the conductive agent SP, and the binder is 90:5:5) and an appropriate amount of solvent NMP are mixed to form a positive electrode slurry; the positive electrode slurry is then coated on a 12 μm thick aluminum foil, and then dried and sliced into circular electrode sheets with a diameter of 12 mm, and the positive electrode sheets, diaphragms, electrolytes, and metal lithium sheets are assembled into CR2032 button batteries in this order. Finally, the capacity retention rate at different rates is tested, specifically, different rate discharge tests are performed, and the test voltage range is 2.5 to 4.2 V. During the test, the battery was charged to 4.2V at 0.3C constant current and constant voltage in a 25°C constant temperature box, with a cut-off current of 0.05C; after standing for 10 minutes, it was discharged to 2.5V at 0.3, 0.5, 1, 3, 4, and 8C rates, respectively. The test results of the capacity retention rate of the lithium iron phosphate electrode materials of each embodiment and comparative example at different rates are shown in Table 2.
[0060] Table 2 Capacity retention rate of lithium iron phosphate electrode materials in various embodiments and comparative examples at different rates
[0061]
[0062]
Claims
1. A method for preparing a lithium iron phosphate electrode material, characterized in that: The following steps are involved: A lithium iron phosphate suspension and a dopamine hydrochloride solution are mixed so that the dopamine hydrochloride self-polymerizes on the surface of the lithium iron phosphate to form polydopamine, and then the solid and liquid are separated, and the solid obtained by solid separation is calcined to obtain a lithium iron phosphate electrode material; the primary particle size of the lithium iron phosphate is 200-400nm, and the ratio of the mass of the lithium iron phosphate in the lithium iron phosphate suspension to the mass of the dopamine hydrochloride in the dopamine hydrochloride solution is (2-3):(0.004-0.02).
2. The method for preparing the lithium iron phosphate electrode material according to claim 1, characterized in that: The primary particle size of lithium iron phosphate is 200-230 nm, and the ratio of the mass of lithium iron phosphate in the lithium iron phosphate suspension to the mass of dopamine hydrochloride in the dopamine hydrochloride solution is 3:(0.010-0.018); the primary particle size of lithium iron phosphate is 250 nm, and the ratio of the mass of lithium iron phosphate in the lithium iron phosphate suspension to the mass of dopamine hydrochloride in the dopamine hydrochloride solution is 3:(0.012-0.015); the primary particle size of lithium iron phosphate is 400 nm, and the ratio of the mass of lithium iron phosphate in the lithium iron phosphate suspension to the mass of dopamine hydrochloride in the dopamine hydrochloride solution is 2:(0.005-0.007).
3. The method for preparing the lithium iron phosphate electrode material according to claim 1, characterized in that: The dopamine hydrochloride solution is prepared by mixing dopamine hydrochloride and a buffer solution, wherein the buffer solution is a tris(hydroxymethyl)aminomethane hydrochloride buffer solution.
4. The method for preparing the lithium iron phosphate electrode material according to claim 1, characterized in that: The carbon content on the surface of lithium iron phosphate is not more than 2%.
5. The method for preparing the lithium iron phosphate electrode material according to claim 1, characterized in that: The mass fraction of the lithium iron phosphate suspension is 2% to 3%.
6. The method for preparing the lithium iron phosphate electrode material according to any one of claims 1 to 5, characterized in that: The lithium iron phosphate suspension and the dopamine hydrochloride solution are mixed for 12 to 16 hours.
7. The method for preparing a lithium iron phosphate electrode material according to any one of claims 1 to 5, characterized in that: The calcination temperature is 650-750°C and the calcination time is 8-12 hours.
8. The method for preparing the lithium iron phosphate electrode material according to claim 7, characterized in that: The heating rate from room temperature to the calcination temperature is 5-10°C / min.
9. A lithium iron phosphate electrode material prepared by the method for preparing a lithium iron phosphate electrode material according to any one of claims 1 to 8.
10. Use of the lithium iron phosphate electrode material prepared by the method for preparing the lithium iron phosphate electrode material according to any one of claims 1 to 8 as a positive electrode material for a lithium battery.
Citation Information
Patent Citations
Method for preparing carbon-coated modified lithium iron phosphate positive electrode
CN117088348A
Cited By
Lithium manganese iron phosphate material and preparation method thereof
CN120348920A
High-temperature-resistant low-iron-dissolution lithium iron phosphate material as well as preparation method and application thereof
CN120664513A